Application of DNA Hybridization Biosensor as a Screening Method for the Detection of Genetically Modified Food Components - Tichoniuk, Mariusz (Molecular Diversity Preservation International (MDPI), 2008)
An electrochemical biosensor for the detection of genetically modified food components is presented. The biosensor was based on 21-mer single-stranded oligonucleotide (ssDNA probe) specific to either 35S promoter or nos terminator, which are frequently present in transgenic DNA cassettes. ssDNA probe was covalently attached by 5′-phosphate end to amino group of cysteamine self-assembled monolayer (SAM) on gold electrode surface with the use of activating reagents – water soluble 1-ethyl-3(3′-dimethylaminopropyl)-carbodiimide (EDC) and N-hydroxy-sulfosuccinimide (NHS). The hybridization reaction on the electrode surface was detected via methylene blue (MB) presenting higher affinity to ssDNA probe than to DNA duplex. The electrode modification procedure was optimized using 19-mer oligoG and oligoC nucleotides. The biosensor enabled distinction between DNA samples isolated from soybean RoundupReady(®) (RR soybean) and non-genetically modified soybean. The frequent introduction of investigated DNA sequences in other genetically modified organisms (GMOs) give a broad perspectives for analytical application of the biosensor.